2011
DOI: 10.1007/s12011-011-8959-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Acute Oral Toxicity Class of Trinuclear Chromium(III) Glycinate Complex in Rat

Abstract: Chromium(III) is considered as an essential element playing a role in carbohydrate and lipid metabolism, and various chemical forms of this element are widely used in dietary supplements. A new trinuclear chromium(III) glycinate complex [Cr3O(NH2CH2CO2)6(H2O)3]+NO3− (CrGly), an analogue of Cr3 (trinuclear Cr(III) propionate complex) has been synthesized as a potential source of supplementary Cr. In this study, we evaluated the acute toxicity class of CrGly in Wistar rats applying the OECD 423 procedure. Male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…Cr w formie organicznej jest lepiej wchłaniany niż w formie nieorganicznej i prowadzi do wzrostu koncentracji tego składnika w tkankach (80). Zauważono, że biodostępność kationu propionianu chromu (CrProp) jest znacznie wyższa w porównaniu do innych popularnych suplementów chromu w diecie, takich jak: chlorek, nikotynian lub pikolinian chromu (23,94,95). CrProp jest absorbowany z dużą skutecznością 40-60% (94,95).…”
Section: Toksykokinetykaunclassified
See 1 more Smart Citation
“…Cr w formie organicznej jest lepiej wchłaniany niż w formie nieorganicznej i prowadzi do wzrostu koncentracji tego składnika w tkankach (80). Zauważono, że biodostępność kationu propionianu chromu (CrProp) jest znacznie wyższa w porównaniu do innych popularnych suplementów chromu w diecie, takich jak: chlorek, nikotynian lub pikolinian chromu (23,94,95). CrProp jest absorbowany z dużą skutecznością 40-60% (94,95).…”
Section: Toksykokinetykaunclassified
“…Zauważono, że biodostępność kationu propionianu chromu (CrProp) jest znacznie wyższa w porównaniu do innych popularnych suplementów chromu w diecie, takich jak: chlorek, nikotynian lub pikolinian chromu (23,94,95). CrProp jest absorbowany z dużą skutecznością 40-60% (94,95). Najwyższą akumulację Cr w tkankach wykazano po podaniu Cr w formie nanocząstek (61,105,112).…”
Section: Toksykokinetykaunclassified
“…Trivalent chromium, the form found in food and dietary supplements, is considered to be safe. Many organic chromium complexes, including chromium picolinate [Cr(Pic) 3 ], chromium nicotinate (NCB) [ 11 , 12 ], chromium histidinate (CrHis) [ 13 , 14 ], chromium complex of d -phenylalanine [Cr( d -Phe) 3 ] [ 15 , 16 ], chromium propionate complex (Cr3) [ 4 , 17 19 ] and chromium glycinate complex (CrGly) [ 19 ], have been synthesised and demonstrated to be biologically effective. Different coordinate ligands of these organic chromium complexes exhibited different bioactive compounds [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first study on the beneficial effect of Cr(III) on the regulation of carbohydrate metabolism was published in the late 1950s when Schwartz and Mertz et al [26] found that Cr(III) appeared to be an essential element in glucose metabolism. Since then, there have been numerous studies on animals [68, 27, 28] and humans [2931], which analysed the role of this element in carbohydrate and lipid metabolism. Many studies on animal-resistant and diabetic animals (mice, rats) showed the therapeutic potential of various supplementary Cr(III) compounds, which regulated disordered carbohydrate and lipid metabolism in diabetes.…”
Section: Discussionmentioning
confidence: 99%